SIKAP MENTAL WIRAUSAHAWAN DALAM MENGHADAPI PERKEMBANGAN ZAMAN - -, Sunarso (Universitas Slamet Riyadi, 2010)
ABSTRACT A needed matter by someone which wish entrepreneur is never give up attitude to situation to realize human being which is taught to be needed by patience, healthy spiritual and corporeal manful. Efficacy can be reached by dint of hard work by majoring personal strength in effort reach the target of life. In reaching target, hence do not always go well as desired. Many barrier and barricade which possibly will be met to overcoming it, hence needed by creative and constructive idea. With such idea hence someone will quickly and wise in taking needed action. Creative idea will assist someone to recognize risk, so that can draw up to with refer to effort to minimize the risk Keywords: entrepreneur, UKM development, corporate world, business.